Development of the Meatball Business in Mutiara District, East Kisaran City - Dardanila, Dardanila; Lubis, Rosliana; Ariani, Farida (Asosiasi Profesi Multimedia Indonesia, 2024)
The purpose of this activity is to develop the meatball sales business by improving production efficiency and empowering entrepreneurial skills, thus supporting the achievement of SDG 8, namely decent work and economic growth. Meatball business is a popular form of entrepreneurship and has many customers. The partner in this activity is a meatball business owner located on Jalan Sultan Alisabana, Mutiara Village, East Kisaran City. Based on interviews with the business owner, two main problems were found: firstly, the absence of entrepreneurship training attended by the business owner, which hinders the development of their business, and secondly, the absence of a meatball molding tool which causes delays in production, especially during times of high demand. To overcome these problems, the methods used include surveys, location determination, FGDs with local communities, procurement of equipment, and training and mentoring related to the use of meatball molding machines. The results of this activity provide partners with an understanding of how to become better entrepreneurs and how to use meatball molding equipment to increase production efficiency. The use of the meatball molding machine succeeded in increasing the amount of production and speeding up the process of making meatballs. This activity also received a positive response from the community because it facilitates the production process and has the potential to increase partner income. Overall, this activity succeeded in improving the partners' production quality and entrepreneurial skills, as well as contributing to local economic growth.